2015
DOI: 10.1002/eat.22419
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional functioning in binge‐eating disorder: A systematic review

Abstract: Overall, the cross-sectional findings indicate BED to be associated with difficulties in CoF and EmF. Future research should determine the nature of these difficulties, in regards to general and disorder-related stimuli, and consider interactions of both domains to foster the development and improvement of appropriate interventions in BED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 113 publications
(316 reference statements)
5
93
2
7
Order By: Relevance
“…Buna göre yeme tutumlarındaki sorunların artışı ile duygudurum bozukluğu belirtileri arasında anlamlı bir ilişki olduğu söylenebilir. Kittel, tıkınırcasına yeme davranışı sergileyen bireylerin normal kilolu ve şiş-man bireylere göre daha fazla duygusal sorun yaşadı-ğını bildirmiştir (9).…”
Section: Duygudurum Bozuklukları öLçeği (Dbö)unclassified
“…Buna göre yeme tutumlarındaki sorunların artışı ile duygudurum bozukluğu belirtileri arasında anlamlı bir ilişki olduğu söylenebilir. Kittel, tıkınırcasına yeme davranışı sergileyen bireylerin normal kilolu ve şiş-man bireylere göre daha fazla duygusal sorun yaşadı-ğını bildirmiştir (9).…”
Section: Duygudurum Bozuklukları öLçeği (Dbö)unclassified
“…Individuals with BED frequently lose control over eating especially in the context of negative mood because they fail to regulate their negative mood in a more healthy way. In other words, affectevoking situations may interact with individuals' emotion regulation strategies (Dingemans et al, 2009a;Svaldi et al, 2014b;Kittel et al, 2015;).…”
Section: Introductionmentioning
confidence: 99%
“…The number of studies which investigated set-shifting in BED specifically is however limited. A more recent systematic review by Kittel et al (2015) included more studies than Wu et al (2014), showing mixed results. Two studies found set-shifting deficits in patients with BED, when compared to matched controls without BED (Duchesne et al, 2010;Svaldi et al, 2010), whereas three other studies found no differences in set-shifting abilities between patients with and without BED (Galioto et al, 2012;Kelly et al, 2013;Manasse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Los défi cits en la toma de decisiones, la infl exibilidad cognitiva, la falta de atención al detalle y las difi cultades en la planifi cación y solución de problemas (Qavam et al, 2015), junto a las difi cultades emocionales para identifi car, describir, expresar y manejar las emociones propias y de los demás (Giel et al, 2016;Kittel et al, 2014), podrían explicar parte de los problemas encontrados en el tratamiento de los pacientes con obesidad, sobre todo en el mantenimiento del peso perdido una vez acabado el tratamiento.…”
Section: Discussionunclassified
“…El grupo de Tchanturia posteriormente y, atendiendo a las difi cultades en la regulación emocional de las pacientes con trastornos alimentarios (Kittel et al, 2014;Caglar-Nazali et al, 2014), desarrolló el programa cognitive remediation and emotion skills training (CREST) , en el que, además de trabajar sobre las difi cultades neuropsicológicas, también lo hace sobre los aspectos socio-emocionales. Hasta la fecha, los pocos estudios que han evaluado su efi cacia están ofreciendo resultados esperanzadores en pacientes con AN Harrison, Mountford, y Tchanturia, 2014).…”
Section: Introductionunclassified